World Bank-Civil Society Engagement : Review of Fiscal Years 2010-2012 - World Bank (World Bank, Washington, DC, 2016)
World Bank relations with civil society continued to expand throughout the institution during 2010–12. This evolution was experienced across the spectrum of the "engagement continuum," which includes information disclosure, policy dialogue, strategy consultations, operational collaboration, and institutional partnerships.